2012
DOI: 10.3892/or.2012.1901
|View full text |Cite
|
Sign up to set email alerts
|

Type III interferon induces apoptosis in human lung cancer cells

Abstract: Abstract. The apoptotic effects of interferon lambdas (IFNλs) have been described in several types of cancers. However, their effects on human lung cancer cells and the mechanisms are elusive. In addition, the interaction between IFNλs and other interferons remains unclear. The interplay between IFNα and IFNλ has been reported. However, although IFNγ is a well-known regulatory interferon, the mechanisms through which it regulates IFNλs in lung cancer cells are unknown. These issues are critical for the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, this result is somewhat different from the results of previous studies. In the previous studies, the expression of IFN λ1 in A549 cells was increased by the transfection of a plasmid expressing IFN λ1, and the proliferation of A549 cells was not affected (Li et al, ). In this study, IFN λ1 was added in the cell culture supernatant, and it affected the proliferation of A549 cells from two aspects, including apoptosis and autophagy, indicating that the route of administration of IFN λ1 might directly affect the therapeutic effect.…”
Section: Discussionmentioning
confidence: 92%
“…However, this result is somewhat different from the results of previous studies. In the previous studies, the expression of IFN λ1 in A549 cells was increased by the transfection of a plasmid expressing IFN λ1, and the proliferation of A549 cells was not affected (Li et al, ). In this study, IFN λ1 was added in the cell culture supernatant, and it affected the proliferation of A549 cells from two aspects, including apoptosis and autophagy, indicating that the route of administration of IFN λ1 might directly affect the therapeutic effect.…”
Section: Discussionmentioning
confidence: 92%
“…IFN-l and also IFN-b treatment induced the expression of KLF6, which would also lead to elevated TGF-b. Treatment with IFN-l causes cell cycle arrest in A549 (Li et al, 2012) and other cell lines (Li et al, 2008(Li et al, , 2010, and may do so via elevated TGF-b. The release of IFN-l during infection may also induce TGF-b expression and cell cycle arrest in neighbouring uninfected cells during RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, induction of KLF6 by IFN-l/IFN-b but not LPS/polyI:C suggested that these cytokines could induce KLF6 expression via the Jak-Stat (Janus kinas-signal transducer and activator of transcription) pathway. Treatment with IFN-l does cause cell cycle arrest at G 0 /G 1 phase in A549 (Li et al, 2012) as well as other cell lines (Li et al, 2008(Li et al, , 2010.…”
Section: Rsv Ns1 Modulates Tgf-b Expression Via Klf6mentioning
confidence: 99%
“…IL28RA is widely present in various tissues of human body, and is highly expressed in organ tissues such as heart, bone marrow, pancreas, thyroid, skeletal muscle, prostate and testis [2] . Studies have shown that IFN-λs can activate JAK-STAT and PI3K/AKT signaling pathways to play antiviral, anti-tumor proliferation roles and regulate in ammatory responses [3][4][5][6][7][8] . IL28RA has has two alternative splicing (AS)variants, namely IL28RAVl and IL28RAV2, both of which can bind to type III interferon, but the latter loses the signal transduction function and can inhibit the activity of IFN-λs, so they have opposite functions [9] .…”
Section: Introductionmentioning
confidence: 99%